Systematic Literature Review: Hubungan Kepuasan Kerja dengan Turnover Intention - Fardeen Naushad Asshidiqie; Azzahra Chaliya Ramdhani; Manda Amelia Putri; Shirley Azi Astuti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
High levels of employee turnover intention pose a significant challenge for organizations as they affect the stability and performance of human resources. One factor that is frequently associated with turnover intention is job satisfaction. This study aims to analyze the relationship between job satisfaction and employee turnover intention based on findings from previous studies. This research employs a Systematic Literature Review (SLR) method by reviewing relevant articles from national and international journals selected through inclusion and exclusion criteria. The results of the literature review indicate that job satisfaction has a negative relationship with turnover intention, meaning that higher levels of job satisfaction are associated with a lower tendency for employees to leave the organization. However, job satisfaction is not the sole factor influencing turnover intention, as other factors such as career development opportunities, working conditions, and labor market dynamics also play a role. Therefore, turnover intention can be understood as a complex phenomenon influenced by multiple interrelated factors, highlighting the importance of comprehensive human resource management strategies to reduce employee turnover intention.